Ferreira, Frederico Castelo - (:unkn) unknown (My University, 2026)
RESEARCH INTERESTS My current research interests, balance between fundamental and applied research, with potential translation into the market of sustainable products and processes. The three current research lines aim at the development of new processes, reactors and materials, with an emphasis on membrane based systems, for: 1. tailored materials to mimicking stem cell microenvironments 2. advanced separations in pharmaceutical industry 3. biorefineries for sustainable aviation biofuels and added value products EDUCATION/QUALIFICATIONS 2006-2008 Master in Business and Administration. Faculdade de Economia, Universidade Nova de Lisboa/ Faculdade de Ciências Económicas e Empresariais, Universidade Católica Portuguesa. 2005-2008 1st Module of the Certificate of Advanced Study in Learning and Teaching (CASLAT). Centre for Educational Development. Imperial College London. Training on High Education Teaching. 1999-2004 Ph.D. in Chemical Engineering. Department of Chemical Engineering and Chemical Technology, Imperial College London. Supervisor: Prof. Andrew Livingston, Examiners: Prof. Robert Field and Prof Kang Li. Thesis title: “Membrane Aromatic Recovery System (MARS): Theoretical Analysis and Industrial Applications”. 2002-2003 PG Certificate of Demonstration, Centre for Educational Development. Imperial College London. Postgraduate Program in supervision and student learning 1993-1999 5-years Undergraduate Degree. Applied Chemistry (major in chemistry, minor in biotechnology). Faculdade de Ciências e Tecnologia, Universidade Nova de Lisboa, Portugal. Award: 16/20. WORK EXPERIENCE Current: 2015 Assistant Professor. Department of Bioengineering, Instituto Superior Técnico, Institute for Bioengineering and Biosciences (IST/IBB), University of Lisbon, Portugal. PAST (Academic) 2013 Associate Researcher, Investigador Principal, Development grant, Investigador FCT, Research Contract: IF/00442/2012 (Starting date: 1 Sept 2013), Main Scientific area: Engineering and Technology, Scientific Area: Chemical engineering. Instituto Superior Técnico, Institute for Biotechnology and Bioengineering (IST/IBB) 2009-2013 Invited Assistant Professor. Department of Bioengineering (2011-2013)/Department of Chemical and Biological Engineering (2009-2010), Instituto Superior Técnico, Institute for Biotechnology and Bioengineering (IST/IBB), Technical University of Lisbon, Portugal, under the MIT-Portugal Program. 2008-2009 Research fellow. Instituto de Ciência e Engenharia de Materiais e Superfícies/Department of Chemical and Biological Engineering (ICEMS/DEQB), Instituto Superior Técnico, Technical University of Lisbon, Portugal. 2006-2008 Post-Doc Researcher. Faculdade de Ciências e Tecnologia, Universidade Nova de Lisboa/Honorary Research Associate: Imperial College London. Project on membrane technology: chiral separations, nanofiltration and water treatment. 2004-2006 Research Associate. Department of Chemical Engineering and Chemical Technology, Imperial College London (IC). United Kingdom. Project in collaboration with GlaxoSmithKline (GSK). Assisting, as a post-doc,five Ph.D. students.. PAST (Industrial and Knowledge Transfer) 2013 Research and Technology Management Fellowship (5 months), SUDOE Regenerative Medicine Network SUDOE Interreg IV B. SOE3/P1/E750. 2008-2013 Business Development Consultant. Supporting Executive for CoHiTec 2008-13, Business catalyst for ISCT-MIT I3 2010 and Building Global Innovators 2013. 2007 Technical consultancy. Membrane Extraction Technology (MET). Development of organic solvent nanofiltration processes. Primary contact: Dr Andrew Boam (6 months). 2002 Development Process Engineering. Membrane Extraction Technology (now Evonik-MET). United Kingdom. Industrial application of the MARS at pilot scale at a resin production site (6 months). AWARDS AND BONUS 2008: 1st prize for knowledge valorization, business plan for 1st phase of CoHiTec programme; 2006: Technology Venture Fellowship, The Entrepreneurship Centre, Tanaka Business School. “New Venture Creation 1: The Entrepreneurial Journey” and “Venture Capital Finance”. 2005 Bonus Award Imperial College London 2006-2009 Honorary Research Associate fellow of Imperial College London 2000-2004 Individual PhD Scholarships. 2006-2008 Post-Doc Scholarships